Pemenuhan Hak Penyandang Disabilitas Dalam Memperoleh Pekerjaan Pada Instansi Pemerintah di Kota Ternate - Salha Marasaoly; Sri Indriyani Umra; Ainurafiqa Pelupessy (Jurnal Interpretasi Hukum, 2025)
Persons with disabilities face numerous barriers, particularly in accessing information, healthcare, transportation, infrastructure, and employment opportunities. This study aims to analyze the fulfillment of the right to work for persons with disabilities in government institutions in Ternate City and to identify the factors that hinder their access to the job market. The 1945 Constitution and Law No. 8 of 2016 on Persons with Disabilities guarantee the right to employment by setting a minimum quota of 2%. However, the implementation of this policy in Ternate City has not yet met the expected target. This research employs a legal and conceptual approach using qualitative methods. The findings identify several key factors that hinder persons with disabilities from obtaining suitable employment, including low levels of education, limited access to job vacancy information, a lack of skills training programs, and low self-confidence due to stigma and discrimination. These findings highlight the crucial role of the government and policymakers in creating a more inclusive work environment.